ANALISIS WACANA PERCAKAPAN SIARAN PASAR SENGGOL CEPET PAYUNE RADIO POP FM SEMARANG - Mohamad Syaefudin; Maksum Suparman (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2017)
This research aims to explain (1) the speaking analysis using Dell Hymes SPEAKING theory; (2) the concept of adjacent pairs (3) turn to speak in a conversation broadcast